A Genetic Algorithm Approach For Design Optimization Of Single-Phase Rectifier Transformer. - Rama Rao, Dr.K.S.; Low, Kah Keat (2005)
This paper presents a design procedure for optilnal design of a semi-conductor rectifier transformcr by Genatic Algorithm.